Seasonal Variation of Zooplankton Abundance and Their Relation to Physical Factors of Ain-Zayanah Lagoon, Benghazi - Souad Alsharef; Abdulhamed Etriieki (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. The physical parameters and the occurrence and abundance of zooplankton in Ain-Zayanah lagoon, Benghazi, Libya, were studied from August, 2005 – July, 2006, as a part of detailed investigation on the feasibility of converting the lagoon into an aquaculture farm for captive breeding and culturing of different economically important edible fish, fish fry, molluscan and crustacean animals, and for culturing the zooplankton which form the food of these organisms. Methods. Five different sites located near to the shore were selected in the lagoon for water and zooplankton monthly sampling and analyses. The physical parameters of the water included air and water temperatures, transparency, electrical conductivity, total dissolved solids, pH, dissolved oxygen and total hardness; they were analysed using standard methods. Various differences were revealed in the relationships of these parameters in and between sites, months and seasons. Results. Seven major groups of zooplankton inhabited Ain-Zayanah lagoon; rotifers formed the dominant one (40.50%), followed by rhabtida (21.61%), crustacean larva (14.55%), foraminifera (13.23%), ostracoda (5.97%), copepoda (4.13%) and cladocera (0.01%). Air and water temperatures, pH, DO, electrical conductivity, TDS and hardness had different relationships with the seven zooplankton groups in Ain-Zayanah lagoon. Conclusion. The results obtained were discussed extensively in the light of available literature in the fields, and suitable conclusions, suggestions and precautions to be taken were given in connection with the establishment of Aquaculture farm in Ain-Zayanah lagoon